Analysis of The Influence of Vehicle Overloading on The Remaining Life of The Road Plan - Putri, Shafira Amalia; Sholichin, Ibnu; Fatikasari, Aulia Dewi (Composite: Journal of Civil Engineering, 2024)
The Sidoarjo East Ring Road is one of the roads in Sidoarjo. Along it are industrial warehouses, which are the main route for heavy vehicles such as trucks carrying large commercial goods. The presence of trucks carrying large commercial goods passing through the Sidoarjo East Ring Road affects the condition of the planned road pavement. Therefore, this research needs to be carried out to find out how much influence overloading has on reducing the design life of the road. This research uses AASHTO 1993 guidelines. There are two types of data: secondary data in the form of average daily traffic and vehicle load data crossing the Sidoarjo East Ring Road and primary data in the form of average daily traffic. From the data obtained, the ESAL value, W18 value, truck factor value, and remaining life of the road plan can be calculated. Based on the data analysis that has been carried out, the standard Î£W18 values are 471678.71 to 3467360.95, and the Î£W18 overload in 2021 is 626066.63 to 4625156.45. If the truck factor value is >1, the Sidoarjo East Ring Road section is experiencing overload due to heavy vehicles. The percentage value of remaining life due to LHR and overload is 7.392%, and in overload conditions, there is a reduction in the planned life of the road by 0.8 years from the planned life of 5 years, where the planned life of the road will end in 2025, the second month since the road opened in 2021.